노인급식제도 개발을 위한 농촌 노인의 식생활 양상 기초조사 - 영양소 섭취 및 건강관련 행동 실태 - ( Nutrient Intakes and Health-related Behaviors of the Elderly in Rural Area ) - 박영숙; 김순; 박기순; 이정원; 김기남 (Korean journal of community nutrition, 1999)
A study about health status of the elderly in rural area was performed with 110 home-bound elderly. The results obtained by questionaires and personal interviews recall were as follows. 1) Subjects were 68.6 years of age on average. They revealed the physical tendency of not overweight but high blood pressure. 2) We found that seniors who live alone in rural area were more than in urban area. 3) Average daily intakes of energy and protein of rural elderly were lower than the Korean RDA and the intakes of Ca, riboflavin and niacin in female were also lower. 4) Nutrient intakes were related to family income, food expense, smoking amount, drinking frequency and duration of exercrse, which suggested the needs of nutrition education for the seniors and meal services especially for the low-income elderly.